Molybdenum disulfide-based hybrid catalysts at the forefront of water treatment: A review of the innovative solutions for effective bacterial disinfection - Farouk A. Rasheed; Monireh Nouri; Tooraj Massahi; Hossein Arabzade; Hekmat M. Ibrahim; Sofia Samoili; Stefanos Giannakis; Masoud Moradi; Kiomars Sharafi; Maryam Mardani; Sherzad M. Ali (Results in Engineering)
Recent advancements in water treatment technologies have highlighted the pressing demand for environmentally friendly and efficient solutions to address waterborne bacterial pathogens. This review highlights the remarkable potential of MoS2-based catalysts for bacterial disinfection applications, stemming from their unique combination of photodynamic, photothermal, and catalytic characteristics. We conducted an extensive literature review to analyze different MoS2 catalysts, focusing on their synthesis, mechanisms of inactivation, and effectiveness in eliminating harmful bacteria such as Escherichia coli and Staphylococcus aureus, with observed elimination rates reaching 100%. Our comparative analysis revealed that MoS2-based catalysts exhibit superior bacterial inactivation efficacy and offer significant environmental and economic advantages, including reduced chemical usage and the potential for scalable applications. The specific results demonstrated the effectiveness of the catalysts under various conditions, highlighting the role of photogenerated reactive intermediates in the inactivation process. This study identifies critical areas for further research, including catalyst optimization, stability assessment, and real-world application feasibility, to fully harness MoS2's potential in water disinfection. Our findings position MoS2-based catalysts at the forefront of innovative solutions for addressing global water treatment challenges.